Correlation between myocardial uptake of technetium-99m-sestamibi and pressure-derived myocardial fractional flow reserve - Morishima, Takayuki; Chikamori, Taishiro; Hatano, Tsuguhisa; Tanaka, Nobuhiro; Takazawa, Kenji; Yamashina, Akira (Journal of cardiology, 2004)
Development of the coronary pressure wire has facilitated the measurement of fractional flow reserve (FFR) to assess the functional severity of coronary artery stenoses. This study evaluated the correlations between FFR and myocardial direct counts of technetium-99m(99mTc)-sestamibi in 20 patients (16 men, 4 women, mean age 66 +/- 8 years) who underwent 99mTc-sestamibi single-photon emission computed tomography (SPECT) with the 2-day protocol using 740 MBq of 99mTc-sestamibi each day. Visual assessment of myocardial imaging and quantitative analysis with the measurement of percent uptake and direct count of 99mTc-sestamibi were performed. Visual assessment of myocardial imaging revealed that reversibility of 99mTc-sestamibi perfusion defects was correlated with FFR of < 0.75, which is regarded as functionally important stenosis (17/20 vs 3/20, kappa = 0.71, p < 0.002). Regional reversibility score did not correlate with FFR (r = -0.40, p = NS). Quantitative analysis revealed that the change in 99mTc-sestamibi percent uptake with pharmacologic stress using adenosine triphosphate disodium (ATP) also did not correlate with FFR (r = 0.35, p = NS). In contrast, percent increase in 99mTc direct counts with ATP was lower in patients with FFR of < 0.75 than in those with FFR of > = 0.75 (-4 +/- 16% vs 24 +/- 30%, p < 0.01). In addition, a significant correlation (r = 0.70, p < 0.001) was observed between percent increase in 99mTc direct counts with ATP and FFR. These results suggest that quantitative analysis of 99mTc-sestamibi scintigraphy enables the assessment of the magnitude of functional significance of coronary stenosis.